Investigation of motorcyclist and pillion passenger injuries using numerical simulations. (March 2019) - Sudyoddee, H.; Behr, M.; Llari, M.; Koetniyom, S.; Carmai, J.
Abstract: Road traffic fatalities involving powered-two wheeler (PTW) are the highest portion in Thailand. Few studies are available concerning the head impact loading and head trauma in case of real PTW accidents. This work, therefore, aims to improve the understanding on kinematics and head trauma of PTWs rider and pillion passengers. By selecting a real-world PTW accident provided by the Central Institute of Forensics Science database, reconstruction of the accident was performed using multibody dynamics simulations. Parametric studies which focused on vehicle speed and position of rider and passenger at impact was conducted to obtain the best correlations. Then, head impact velocity, impact direction and head impact area have been extracted and implemented in the finite element head model to simulate the head trauma by impacting directly the head model on the vehicle structure. The motorcyclist's head and the pillion passenger's head impact conditions were retrieved and used as initial condition for the finite element head impact simulation. Head and brain injuries were analyzed.